2012
DOI: 10.1111/j.1365-2826.2011.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Affects Reproductive Functions in Female Diet‐Induced Obese and Dietary Resistant Rats

Abstract: BACKGROUND Incidence of ovulatory disorders is common in obese animal models. The mechanism behind this effect is not clear. We hypothesized that high fat (HF) diet induces alterations in neuroendocrine mechanisms resulting in anovulation in diet-induced obese (DIO) animals. METHODS Adult female DIO and diet-resistant (DR) rats were fed either chow or HF diet (45% calories from fat) for 6 weeks. Oestrous cyclicity and body weight were monitored regularly. At the end of treatment, rats were implanted with a j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 45 publications
8
45
1
Order By: Relevance
“…On the other hand, it has been suggested that an increase in serum leptin concentration may have a role in the steroidogenesis of pre-and post-ovulatory follicles: leptin suppresses estradiol production and interferes with the development of dominant follicles and oocyte maturation (Moschas et al, 2002). Thus, the absence of ovulation observed in non-ovulated mated females may be related to leptin concentrations, in accordance with other authors that showed how an elevation in leptin levels is likely to cause a reduction in secretion by decreasing LH production by the pituitary, also preventing the release of the oocytes from the preovulatory follicles (Duggal et al, 2000;Brecchia et al, 2006;Balasubramanian et al, 2012). Our results also showed an increase in BOHB in non-ovulated females.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, it has been suggested that an increase in serum leptin concentration may have a role in the steroidogenesis of pre-and post-ovulatory follicles: leptin suppresses estradiol production and interferes with the development of dominant follicles and oocyte maturation (Moschas et al, 2002). Thus, the absence of ovulation observed in non-ovulated mated females may be related to leptin concentrations, in accordance with other authors that showed how an elevation in leptin levels is likely to cause a reduction in secretion by decreasing LH production by the pituitary, also preventing the release of the oocytes from the preovulatory follicles (Duggal et al, 2000;Brecchia et al, 2006;Balasubramanian et al, 2012). Our results also showed an increase in BOHB in non-ovulated females.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these results suggest that problems due to LH secretion or to LH follicular receptors can be discarded. Moreover, Balasubramanian et al (2012) showed that lower LH levels impair ovulation process, causing a lower number of fresh corpora lutea, as we detected in this work.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The reason for the reduction in plasma estradiol levels is not clear. However, Balasubramanian et al (2) reported that HFD exposure increases serum leptin levels in the DIO group and that elevated leptin levels can impair ovulation and cause a reduction in estradiol synthesis in the ovary, resulting in inversely decreased estradiol levels. Further studies are needed to prove that HFD-induced increase in leptin levels is responsible for the decrease in estradiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Balasubramanian et al reported that a 6-week HF diet, where 45% of calories came from fat, reduced the concentration of oestradiol in female rats [67].…”
Section: Interestingly Mariappan Et Al Reported Increased Nfκb Exprmentioning
confidence: 99%